Experimental Study on the Behavior of Bounded Square Footing on Sandy Soil - Mohammed Y. Fattah; Kais T. Shlash; Husham A. Mohammed (Engineering and Technology Journal, 2014)
Structural skirts are walls fixed to the edges of shallow foundations to improve their bearing capacities. Sometimes, the shallow foundation is bounded by a close obstruction like a wall. The presence of this wall has an effect on the bearing capacity of footing, whose behavior in this case can be similar to a skirted foundation in which a structural skirt is located at one side of the footing. The present study investigates the behavior of model footings bounded by a wall of different depths and located at different distances from the footing, resting on sandy soil. In this study, different parameters are considered such as relative density of sand (33 and 56) %, distance from wall to the edge of footing to width of footing ratio (h/B) (zero, 0.5, 1, 1.5 and 2) and depth of wall to width of footing ratio (d/B) (0.5, 1, 1.5 and 2). Test results show that the presence of the wall affects remarkably the values of bearing capacity, leading to improvement in the values of bearing capacity with different percentages according to the distance from wall to the edge of footing to width of footing ratio (h/B) and depth of wall to width of footing ratio (d/B) due to the increase in soil confinement underneath the footing. In loose sand, the largest improvement in bearing capacity for square footing bounded by walls reaches (43) %, at (h/B = 0.5) and (d/B = 2). In medium sand, the largest improvement in bearing capacity for square footing bounded by walls reaches (56) %, at (h/B = 0.5) and (d/B=2). The bearing capacity increases with depth of the wall, the maximum effect of the wall on the bearing capacity is when the value of the depth of the wall (d/B) is between (1.5-2.0), for square footing on sand of different densities.